Determining the Prevalence of Subclinical Hypothyroidism in Children and Adolescents and its Association with Hyperlipidemia - Prasad DKV; Prabhakara Rao TS; Kiranmai Ch (New Horizons in Medicine and Medical Research Vol. 5, 2022)
The current study sought to determine the prevalence of thyroid dysfunction, particularly subclinical hypothyroidism (SCH), in children and adolescents in northern Andhra Pradesh, as well as its relationship with hyperlipidemia. Some clinicians consider SCH as a benign normal variation and thyroid hormone can be supplemented to lower the TSH levels and the exact cause of TSH elevation is unknown. A retrospective study of 600 subjects (Children=272, Adolescents=328) between 6-19 years of age were included and the following parameters were examined: age, sex, total triiodothyronine (tT3), total tetraiodothyronine (tT4), thyroid stimulating hormone (TSH), total cholesterol, triglycerides (TGL), LDL and HDL cholesterol. The subjects were divided into two groups based on their age (in years), with those aged 6 to 12 years in group I and those aged 12 to 19 years in group II. Thyroid dysfunction was found to be prevalent in 9.9 percent and 10.4 percent of the 272 children and 328 adolescents studied, respectively. Subclinical hypothyroidism was found in 7.7 percent of children and 4.9 percent of adolescents. Females were more affected by thyroid dysfunction than males in both groups. When compared to euthyroid participants, SCH subjects had significantly higher serum levels of total cholesterol, TSH, and TGL (p<0.05).When compared to euthyroids, SCH had statistically significant reduced levels of HDL cholesterol (p<0.05). Between SCH and euthyroids, there was no difference in total T3, total T4, or LDL cholesterol levels. The prevalence of thyroid dysfunction in the study population was found to be 10.2 percent. SCH was found in 7.7 percent of children and 4.9 percent of adolescents, respectively. With a prevalence of 6.2 percent, subclinical hypothyroidism (SCH) was the most common thyroid dysfunction found in our study population (both children and adolescents).